2018
DOI: 10.9745/ghsp-d-18-00271
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Strategies in Financing Health Care for Universal Health Coverage in Low- and Middle-Income Countries

Abstract: The development and adoption of effective digital health financing solutions that fit well in both coherent digital health information architectures and the universal health coverage agenda will require strong partnerships between entrepreneurs, developers, implementers, policy makers, and funders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…From a UHC perspective, NHIF coverage may need to be extended to the informal sector by probably making it compulsory rather than voluntary. Voluntary health insurance may not be a route to achieve UHC . Compulsory means that it may have to not only cover the formally employed but all residents of a country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a UHC perspective, NHIF coverage may need to be extended to the informal sector by probably making it compulsory rather than voluntary. Voluntary health insurance may not be a route to achieve UHC . Compulsory means that it may have to not only cover the formally employed but all residents of a country.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main challenges with voluntary health insurance is high transaction costs for enrolling and paying premiums especially in sparsely populated rural areas . Approximately 74% of the Kenyan population reside in rural areas while 40.1% of rural dwellers live in poverty .…”
Section: Introductionmentioning
confidence: 99%
“…In order to be strategic, purchasers should focus on (i) identifying the best value, (ii) selecting the right providers, (iii) designing smart contracts, (iv) efficiently enforcing such contracts. Under this, the role of provider payment mechanisms and the best use of information (through data, digital solutions and learning - [8]) are deemed to be essential to support strategic purchasing. The potential for strategic purchasing to also reduce fragmentation is acknowledged i .…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…The focus group advocated for removal of all forms of authorization while Onoka et al, (2016) findings concluded on strict adherence to the NHIS operational guideline and penalty for defaulting HMOs. In the course of finding solutions to the problem of moral abuse in the demand for services, Meesen (2018) showed that the management of the insurance scheme has been made more efficient through the use of digital technologies that support enrolment, referral, renewal, claims and feedback. The insurance management information system (IMIS) specifically addresses the insurance challenges in both the formal and informal sector and is flexible to meet different user needs and technical requirement.…”
Section: Discussionmentioning
confidence: 99%